DISTILASI UAP MINYAK KULIT LEMON (Citrus Limon) DENGAN VARIASI SUHU DAN WAKTU PRETREATMENT - Muyassaroh; aurelia nabila fauzi; Darma, Muhammad Jiddan Ali (jurnal ATMOSPHERE, 2023)
Essential oils are often also referred to as Essential Oils, Etherical Oils, or Volatile Oils, which are compounds that are volatile and insoluble in water and have natural extracts from plants derived from leaves, flowers, wood, seeds, roots, as well as fruit skin. Lemon oil is an essential oil that is obtained from the distillation of lemon peel and is used as an aromatherapy oil to cure several disorders such as headaches and nausea. The main content of lemon peel oil is limonene, which is about 94%, besides that there are other compounds such as terpenes, sesquiterpenes, aldehydes (about 3.4-3.6 n-citronella citral) and esters (about 1% geranyl acetate). Steam distillation is a separation process to produce lemon peel oil which is separated by distillation, the steam is obtained by distillation which is carried out at 96 oC, for 1.5-2 hours. The variables used were pretreatment temperature: 30 oC, 45 oC, 60 oC, 75 oC, 90 oC and pretreatment time: 1.5 hours, 2 hours, 2.5 hours, and the best results obtained for lemon peel oil were for material treatment at 1.5 hours. with a temperature of 45oC with Limonene content of 36.714%, α-Pinene 2.678%, and yield 0.0659%.